Efeitos da prática da natação adaptada sobre o perfil bioquímico e o estado de condicionamento físico de indivíduos com lesão medular - De Almeida, Patricia A.; Barbosa, Valéria R. C.; Dias, Matheus C.; Neiva, Cassiano M. [UNESP] (My University, 2011)
Introduction: The lack of physical exercises generated by immobilization of the lower limbs leads to changes in body composition that are generally associated with the imbalance of metabolic rate coupled with a sedentary status, which can result in obesity, diabetes mellitus and cardiovascular disease. Therefore, the improvement of physical fitness can contribute to promoting health and quality of life for these patients. As there is a very small number of research in this direction, our purpose was to investigate the effects of an adapted swimming program in protocol interval, for people with spinal cord injury, aiming to verify the improvement of your fitness and, consequently, some biochemical variables important for health. Methodology: The study included 17 subjects with spinal cord injury, sedentary, divided into two groups: 11 participants in the training group (TG) and 6 in control group (CG). TG was applied by a protocol of interval training in swimming for eight consecutive weeks, three times a week. The protocol employed a stroke of breaststroke in work periods of moderate to severe, and stroke in the backstroke, in periods of active recovery. The CG has not participated in any physical activity. Both groups were collecting blood for biochemical analysis, before (evaluation) and after (revaluation) the swimming program. Results and Discussion: The concentrations of triglycerides, total cholesterol and LDL-cholesterol showed no significant changes in assessment for reassessment in both groups. However the TG, the level of HDL-cholesterol were significant differences (p=0,0110), showing an improvement in posttraining, which did not occur in the CG. With respect to the state of fitness, the results revealed a significant difference in relation to time and distance covered in water when compared with the pre-training (p<0,001), showing a great improvement in the ability to shift with the stroke of breaststroke and a significant improvement in cardiorespiratory function. Conclusion: The swimming program interval used, with moderate to severe intensity, can even in a short period of time, promote positive changes in HDLcholesterol in individuals with spinal cord injury studied, and substantially improve your fitness.
The effects of adaptated swimming program on the biochemstry blood profile and physical fitness in individuals with spinal cord injury
Keywords: Cholesterol, HDL; Health promotion; Interval training; Physical fitness; Spinal cord /injuries; Swimming; cholesterol; low density lipoprotein cholesterol; triacylglycerol; biochemistry; cholesterol blood level; clinical article; clinical assessment; controlled study; fitness; heart function; human; methodology; physical activity; respiratory function; spinal cord injury; swimming; triacylglycerol blood level